Carbon Stock Analysis of Family Fabaceae in the Forest Area of Surabaya State University as An Effort to Conserve the Environment - Rohmah, Tri Lestari Saidha; Fida Rachmadiarti (Universitas Negeri Surabaya, 2025)
Forest vegetation plays a crucial role in mitigating global climate change through carbon sequestration. The Universitas Negeri Surabaya campus forest has significant potential as a carbon sink, particularly through tree species belonging to the Fabaceae family. This study aimed to analyze carbon stocks in Fabaceae trees within the campus forest as an effort toward environmental conservation. Carbon stock estimation was carried out using a non-destructive approach through allometric equations, focusing only on above-ground biomass. The research was conducted in the campus forest area targeting Fabaceae species. Parameters measured included tree trunk diameter at 1.3 meters above ground level, secondary data on wood specific gravity, and leaf chlorophyll content. Data analysis was performed using the Pearson correlation test to determine the relationship between morphological and physiological characteristics of trees and their stored carbon stock. The results showed that the Unesa campus forest contained 4 species and 52 individual trees. The average carbon stock per tree was 213.96 kg C tree⁻¹ year⁻¹, and the total carbon stock in the observed area reached 992.79 kg/ha. Pearson correlation results indicated a positive relationship between morphological and physiological characteristics and carbon stock (Sig. 0.31). Based on these findings, Fabaceae species are recommended as effective contributors to environmental conservation strategies to reduce carbon emissions. These trees also support campus greening programs and align with the achievement of Sustainable Development Goals (SDGs).